A BNCC e a prática pedagógica da língua inglesa para o ensino fundamental - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2024)
The objective of this work is to presente a reflective analysis of the new perspective proposed by the Common National Curricular Base (BNCC) for the teaching and learning English in elementary school. This analysis highlights the emphasis the document places on the English language as a língua franca, as well as the three teaching implications and the organizational axes for the pedagogical develoment of English language learning for this education stage. The methodology used for this study was bibliographic. We analyzed the BNCC and Other authors, but the emphasis was on the BNCC because it was the object of the research. In this paper, we aim to clarify the importance of the formative nature of integral education, wich includes literacy as a linguistic foudation for acquaring a foreign language and providing studentes with a linguistic formation that ensures their proficiency in English. Students should be able to speak English fluently, and for that, it is time to renew Brazilian education. This renewal is achievable by following BNCC guidelines. The result of this study translates into the desire to use the tools offered by the BNCC, wich treats English as a língua franca, to help students listen, speak, write, and read in English whithout excessive concern for accents.
Keywords: Ferramenta BNCC; Ensino e aprendizagem; Eixos organizadores; Inglês; CNPQ:: LINGÜÍSTICA, LETRAS E ARTE